A squeeze on the perovskite structure improves the thermoelectric performance of Europium Calcium Titanates. (December 2018) - Xiao, X.; Widenmeyer, M.; Mueller, K.; Scavini, M.; Checchia, S.; Castellano, C.; Ma, D.; Yoon, S.; Xie, W.; Starke, U.; Zakharchuk, K.; Kovalevsky, A.; et al.
Abstract: Polycrystalline Eu1– x Ca x TiO3– δ (0 ≤ x ≤ 1) samples were synthesised to investigate the interrelations among the crystal structure, local structural disorder, and thermoelectric properties. The Ca 2+ substitution is locally modifying (squeezing) the crystal structure, resulting in distinct differences between the long-range and local scales, e.g., the sample with x = 0.2 shows a cubic structure in long-range scale, while tetragonal distortions are observed locally. Additionally, the contraction of the unit cell volume with an accompanying reduction of the overall symmetry facilitates the accommodation of smaller Eu 3+ (instead of Eu 2+ ). The lattice imperfections induced by Ca 2+ substitution significantly improve electron concentration and simultaneously dramatically reduce thermal conductivity (i.e., as large as 50% compared with pristine sample) at room temperature. The average thermoelectric figure of merit of Eu0.2 Ca0.8 TiO3– δ is enhanced by almost 100% compared with that of the pristine EuTiO3 . This work demonstrates that controlling lattice deformation offers new ways to enhance the thermoelectric performance of titanates. Graphical abstract: Highlights: For Eu1-x Cax TiO3– δ, the Ca 2+ substitution results in distinct differences between the long-range and local scales. Ca 2+ substitution modifies the band structure of Eu1-x Cax TiO3– δ compounds. Ca 2+ substitution significantly improve electron concentration and simultaneously dramatically reduce thermal conductivity. with The average thermoelectric ZT of Eu0.2 Ca0.8 TiO3– δ is enhanced by almost 100% compared with that of the pristine EuTiO3 .